Pelatihan Penganggaran Modal Kerja Berbasis Digital Untuk Komunitas UMKM dan Start-Up - Sita Deliyana Firmialy; Sherly Artadhita; Yogi Suprayogi; Dematria Pringgabayu; Putra Tri Akram (JURNAL PENGABDIAN MASYARAKAT AKADEMISI, 2024)
Through web-based business applications, it helps start-up companies to reach their target markets more quickly and in a more organized manner, with a more efficient level of economic costs compared to using conventional consumer marketing methods which require higher levels of economic costs. However, more than 40% of SMEs and startup companies in Indonesia, both digital and non-digital based, experience financial failure and fail to maintain their business continuously, due to inefficient management of the financial aspects of the organization, which becomes an obstacle for business actors in planning and can also disrupt the level of continuity of the business. This is the background for the need for community service activities in order to improve the quality of financial inclusion, especially in terms of working capital management budgeting for mobile-based SMEs and startup companies. This community service activity was formed to expand knowledge regarding effective and efficient working capital management budgeting, where it is hoped that through this program, mobile-based SMEs and startup business actors will have the knowledge to know the financial strength of their business and can be used as a consideration in decisions and make the business run healthier in the future.